Analisis Faktor Faktor Yang Berpengaruh Terhadap Harga Saham Pada Perusahaan Properti Yang Terdaftar Di Bursa Efek Indonesia - Topan Siswanto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to analyze the Inflation Rate, Interest Rate, Exchange Rate (KURS), and Gross Domestic Product (GDP) of the Composite Stock Price Index (CSPI) (Case Study in the Sector of Property Companies Listed on the Indonesia Stock Exchange for the 2016-2016 period). 2021). This research is associative by linking the independent variable to the dependent variable. The data collection technique uses documents. The results showed that the inflation variable (X1) had a significant effect on the JCI with a t-count value of -6.977 and a significance value of 0.005. The interest rate (X2) has a significant effect on the JCI with a t-count value of 4.883 and a significance value of 0.006. The exchange rate (X3) has a significant effect on the JCI with a t-count value of -11.415 and a significance value of 0.000. Gross Domestic Product (X4) has no significant effect on the JCI with a t-count value of 1.352 and a significance value of 0.178. Simultaneously, all independent variables (inflation, interest rates, exchange rates, and gross domestic product) together have a significant effect on the JCI with a calculated F value of 35.573 and a significance level of 0.000 less than 0.05. The adjusted R square value of 0.436 means that the variables of inflation, interest rates, exchange rates, and gross domestic product explain the JCI variable of 43.6%. The beta coefficient test results show that the exchange rate has the largest coefficient value of -0.655 from the other independent variables. Multiple linear regression equation Y= 1.008 - 1.305X1 + 0.922X2 – 2.780X3 + 0.050X4 + ε